Guidelines for reporting secondary findings of genome sequencing in cancer genes: the SFMPP recommendations. (December 2018) - Pujol, Pascal; Vande Perre, Pierre; Faivre, Laurence; Sanlaville, Damien; Corsini, Carole; Baertschi, Bernard; Anahory, Michèle; Vaur, Dominique; Olschwang, Sylviane; Soufir, Nadem; Bastide, Noëlle; Amar, Sarah; et al.
Abstract In oncology, the expanding use of multi-gene panels to explore familial cancer predisposition and tumor genome analysis has led to increased secondary findings discoveries (SFs) and has given rise to important medical, ethical, and legal issues. The American College of Medical Genetics and Genomics published a policy statement for managing SFs for a list of genes, including 25 cancer-related genes. Currently, there are few recommendations in Europe. From June 2016 to May 2017, the French Society of Predictive and Personalized Medicine (SFMPP) established a working group of 47 experts to elaborate guidelines for managing information given on the SFs for genes related to cancers. A subgroup of ethicists, lawyers, patients' representatives, and psychologists provided ethical reflection, information guidelines, and materials (written consent form and video). A subgroup with medical expertise, including oncologists and clinical and molecular geneticists, provided independent evaluation and classification of 60 genes. The main criteria were the "actionability" of the genes (available screening or prevention strategies), the risk evaluation (severity, penetrance, and age of disease onset), and the level of evidence from published data. Genes were divided into three classes: for class 1 genes (n = 36), delivering the information on SFs was recommended; for class 2 genes (n = 5), delivering the information remained questionable because of insufficient data from the literature and/or level of evidence; and for class 3 genes (n = 19), delivering the information on SFs was not recommended. These guidelines for managing SFs for cancer-predisposing genes provide new insights for clinicians and laboratories to standardize clinical practices.